Egg laying patterns and structure of egg-batches of pine processionary moth Thaumetopoea wilkinsoni in Isparta pine forests - Mustafa Avcı; Sefa Gizem Ölmez (İstanbul Üniversitesi Orman Fakültesi Dergisi, 2016)
In this study, the structure of egg batches laid by Thaumetopoea wilkinsoni, rates of hatching and parasitism, egg parasitoids and the egg-laying patterns of the insect were investigated. A total of 654 egg-batches were collected from 16 pine forests located in Isparta. It was found that the average number of eggs in these sites was 221,2, the average number of eggs that hatched was 80,0% and the rate of parasitism was 13,8%. The average number of eggs at the upper, middle and lower elevations was found to be 208,1, 223,3 and 226,7, respectively, while the rate of hatching was 73,3%, 82,6%, 85,3%, the rate of parasitism was 15,9%, 9,8%, and 8,9%, respectively. The average number of eggs in the batches collected within and at the borders of the stands was found to be 203,9 and 217,6, the rate of hatching was 77,0% and 67,4%, the rate of parasitism was 15,7% and 24,9%, respectively. The egg-laying pattern in both sites was investigated according to the aspect of the egg-batches on trees and lower and upper parts of the canopy of trees. The egg-batches were laid on the northern, western, southern and eastern aspects by 6,5%, 14,7%, 16,7% and 62,2%, respectively. 43,5% of the egg-batches were laid in the lower parts of trees, while 56,5% on the upper parts. The average number of eggs in the batches collected from the lower and upper parts of trees was 195,5 and 197,7, the rate of hatching was 62,5% and 56,5%, and the rate of parasitism was 29,9% and 35,6%, respectively.